2016
DOI: 10.1371/journal.pone.0155401
|View full text |Cite
|
Sign up to set email alerts
|

Have LEGO Products Become More Violent?

Abstract: Although television, computer games and the Internet play an important role in the lives of children they still also play with physical toys, such as dolls, cars and LEGO bricks. The LEGO company has become the world’s largest toy manufacturer. Our study investigates if the LEGO company’s products have become more violent over time. First, we analyzed the frequency of weapon bricks in LEGO sets. Their use has significantly increased. Second, we empirically investigated the perceived violence in the LEGO produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…For example, boys' toys generally include guns, bombs, swords, and military equipment that could all be used to "kill others." Interestingly, a recent study by Bartneck, Min Ser, Moltchanova, Smithies and Harrington (2016) showed that LEGo products have become more violent over time, supporting the claim that masculine toys may be more associated with aggression.…”
Section: Masculine Toys and Playmentioning
confidence: 66%
“…For example, boys' toys generally include guns, bombs, swords, and military equipment that could all be used to "kill others." Interestingly, a recent study by Bartneck, Min Ser, Moltchanova, Smithies and Harrington (2016) showed that LEGo products have become more violent over time, supporting the claim that masculine toys may be more associated with aggression.…”
Section: Masculine Toys and Playmentioning
confidence: 66%
“…Our results confirm the less formal analysis of [ 17 ]. A more detailed analysis of the LEGO colors is available [ 18 ]. He concluded that the exact definition of the colors that TLG is using is unclear and the colors used in this article can only be considered an approximate symbolic representation of the real LEGO colors.…”
Section: Resultsmentioning
confidence: 99%
“…For example, even the company that makes nerf has made many of their soft toys into weapons, which was not the case when the company was founded (Brown et al, 2009). Bartneck, Min Ser, Moltchanova, Smithies, and harrington (2016) found an increase in the presence of weapons in LEGo sets from 1978 (when the first weapon brick was created) to 2014, when about 30% of LEGo sets had a weapon brick. Raters also perceived LEGo to be more violent across time.…”
Section: "War Toys" and Aggressionmentioning
confidence: 95%